Move Analysis of Conclusion Section of Aerospace Research Article (Global Journal of Human-Social Science, 2023)
This paper reports on the move analysis of the conclusion section of the aerospace English research article RA The results are based on the identification of 50 pieces of aerospace conclusion section of RA published in two leading journals that were written by English native writers from 2018 to 2023 Yang Allison 2003 and Zhiqing Hu 2007 s model are the starting point for the analysis Then the major Moves and Steps were extracted and the frequencies were calculated which attempts to provide a modified model for aerospace research articles conclusion section The results reveal that the aerospace conclusion section has three major Moves which are Move 1 Summary of study Move 2 evaluation of study Move 3 suggestion for future research Most of the conclusions have Move 1 and Move 2 This study aims at improving the genre awareness of novice and non-native researchers in order to facilitate their disciplinary writing publishing and reading
Keywords: genre analysis; move analysis; research article; conclusion section; aerospace